Salt Dependent Association of Novel Mutants of TATA-Binding Proteins to DNA: Predictions from Theory and Experiments (Communications in Computational Physics, 2008)
The nonlinear Poisson-Boltzmann predictions of the salt-dependent association of proteins to DNA, SKpred, are fairly insensitive to the choice of atomic charges,radii, interior dielectric constant and treatment of the boundary between a biomoleculeand the solvent. In this study we  show that the SKpred is highly correlated with the conformational adaptability of the partners involved in the biomolecular binding process. This is demonstrated for the wild-type and mutant forms of the archaeon Pyrococcus woesi TATA-binding protein (PwTBP) in complex with DNA, on which we performed molecular mechanics energy minimizations with different protocols, and molecular dynamics simulations and then computed the SKpred on the resulting structures. It was found that the inter-molecular non bonded force field energy between the DNA and protein correlates linearly and significantly well with the SKpred. This correlation encompasses the wild-type and mutant variants of the PwTBP and provides us with a quick way to estimate the SKpred from a large ensemble of structures generated with Molecular Dynamics or Monte Carlo simulations. The corresponding experimental SKobs should also correlate with the inter-molecular non bonded force field energy between the protein and DNA, given that the underlying mechanisms in binding and salt-dependent effects are in fact the main contributors in the association of proteins/peptides to nucleic acids. We show that it is possible to fit experiments versus the inter-molecular non bonded force field energy between the protein and DNA, and use this relation to predict the SKobs in absolute numbers. Thus, we present two novel approaches to estimate both the SKpred and the SKobs for in silico modelled PwTBP novel mutants and even for TBPs from other organisms. This is a simple but powerful tool to suggest new experiments on the TBP-DNA type of macromolecular assemblies. We conclude by suggesting some mutants and a possible biological interpretation of how changes in solvent salinity affect the binding of proteins to DNA.